Expert System for Diagnosing Indihome Network Connection Disorders Using Metode Backward Chaining (Case Study: Telkom Jayapura City) - Abidondifu, Yonas; Kiswanto, Rahmat H.; Sutejo, Heru (International Journal Software Engineering and Computer Science (IJSECS), 2024)
: In the rapidly advancing digital era, reliable internet connectivity has become a fundamental necessity for both individuals and organizations, facilitating various aspects of daily operations. However, technical issues in the network can lead to significant disruptions, adversely affecting productivity and user experience. PT Telkom Access (PTTA) Papua, a subsidiary responsible for managing network infrastructure, often encounters challenges in resolving customer complaints efficiently. A primary issue is the insufficient and vague information provided by customers, which hinders the diagnostic process and prolongs the resolution time. To address this problem, this study proposes the development of an expert system employing the backward chaining method. This system is designed to analyze the symptoms reported by customers and generate precise diagnostic solutions. In addition to offering accurate problem-solving capabilities, the system also aims to improve customer understanding through targeted educational tools, ensuring that essential components are readily available on-site to expedite the repair process. Comprehensive testing of the system has confirmed that all functionalities operate as expected. Consequently, this expert system is projected to significantly enhance customer satisfaction, improve the efficiency of issue resolution, and elevate the overall service quality provided by PTTA Papua.